Head and Neck Cancer Cell Death due to Mitochondrial Damage Induced by Reactive Oxygen Species from Nonthermal Plasma-Activated Media: Based on Transcriptomic Analysis. (7th July 2021) - Oh, Chan; Won, Ho-Ryun; Kang, Woo Seok; Kim, Dae-Woong; Jung, Seung-Nam; Im, Mi Ae; Liu, Lihua; Jin, Yan Li; Piao, Yudan; Kim, Hae Jong; Kang, Yea Eun; Lee, Min Joung; et al.
Abstract : Mitochondrial targeted therapy is a next-generation therapeutic approach for cancer that is refractory to conventional treatments. Mitochondrial damage caused by the excessive accumulation of reactive oxygen species (ROS) is a principle of mitochondrial targeted therapy. ROS in nonthermal plasma-activated media (NTPAM) are known to mediate anticancer effects in various cancers including head and neck cancer (HNC). However, the signaling mechanism of HNC cell death via NTPAM-induced ROS has not been fully elucidated. This study evaluated the anticancer effects of NTPAM in HNC and investigated the mechanism using transcriptomic analysis. The viability of HNC cells decreased after NTPAM treatment due to enhanced apoptosis. A human fibroblast cell line and three HNC cell lines were profiled by RNA sequencing. In total, 1 610 differentially expressed genes were identified. Pathway analysis showed that activating transcription factor 4 (ATF4) and C/EBP homologous protein (CHOP) were upstream regulators. Mitochondrial damage was induced by NTPAM, which was associated with enhancements of mitochondrial ROS (mtROS) and ATF4/CHOP regulation. These results suggest that NTPAM induces HNC cell death through the upregulation of ATF4/CHOP activity by damaging mitochondria via excessive mtROS accumulation, similar to mitochondrial targeted therapy.